Exploring Perceptions and Preventive Practices Related to COVID-19 Among General Public: A Cross Sectional Analytical Study from Pakistan - Tariq, Naseer Alam; Awan, Bushra Ameer Saeed; Rafie, Muhammad; Majeed, Sara; Yousaf, Hafsa; Tayyab, Muhammad; Sahar, Seemabia (Pakistan Armed Forces Medical Journal, 2024)
Objective: This research was done to assess the level of public awareness, perceptions and practices using a survey questionnaire of COVID-19 in Pakistan.Study Design: Cross-sectional analytical study.Place and Duration of Study: Study was carried out from the Nov 2021 to Apr 2022 through online survey in PakistanMethodology: The sample size calculated with open epi sample size calculator was 345. Convenient sampling technique was used. Individuals who consented and between 15 and 80 years of age were included. The questionnaire included Sociodemographic information and questions on respondents' perceptions and preventive practices regarding COVID-19,including particular inquiries about widespread misconceptions.Results: Mean age of the participants was 31±13 years. Proportions of males 159(46%) and females 186(54%) were almost equal, Majority 124(36%) were of age group 21-30 years. Half 172(50%) were graduates and 163(47%) came to knew about COVID-19 from social media Significant association between gender and source of information (p=.008) knowledge of specific cure p=0.040, maintaining social distancing p=0.002), wearing masks in public p=0.003, sanitize personal items (p=0.034)Significant association was found between age categories and source of information p